2007
DOI: 10.1063/1.2750528
|View full text |Cite
|
Sign up to set email alerts
|

Surface-plasmon-enhanced transmission through metallic film perforated with fractal-featured aperture array

Abstract: A fractal-featured metallic thin film with Sierpinski Carpet pattern is fabricated on silicon wafer by microfabrication techniques. Transmission infrared spectroscopy indicates that there exists extraordinary high transmission at specific wavelengths, which can be ascribed to the effect of surface plasmon resonance, and are determined by hierarchy of apertures of different sizes in the fractal structure. This patterned film provides a unique system to achieve enhanced transmission simultaneously at different s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
32
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 31 publications
0
32
0
Order By: Relevance
“…It is found that the enhanced optical transmission through periodic metal hole arrays originates from the resonance of surface Plasmon mode, which is a surface wave generated by the interaction between the surface charge oscillation and the electromagnetic field of the light. The enhancement also depends on the array geometry (diameter, periodicity, and thickness of the metal film), light wavelength, angle of incidence, as well as material of a film [6][7][8][9][10]. For periodic slit arrays, Porto et al [11], who base their arguments on the transfer matrix formalism claim that surface plasmon excitation enhances the efficiency.…”
Section: Introductionmentioning
confidence: 96%
“…It is found that the enhanced optical transmission through periodic metal hole arrays originates from the resonance of surface Plasmon mode, which is a surface wave generated by the interaction between the surface charge oscillation and the electromagnetic field of the light. The enhancement also depends on the array geometry (diameter, periodicity, and thickness of the metal film), light wavelength, angle of incidence, as well as material of a film [6][7][8][9][10]. For periodic slit arrays, Porto et al [11], who base their arguments on the transfer matrix formalism claim that surface plasmon excitation enhances the efficiency.…”
Section: Introductionmentioning
confidence: 96%
“…[9][10] These fantastic properties facilitate potential applications in extraordinary optical transmission, [11][12][13][14][15] microscopy, 16 and antennas, 17 etc.. Among the massive researches in this rapidly developing area, one of the intensively studied subjects is chiral metamaterial, which offers an alternative approach to realize negative refractive index.…”
mentioning
confidence: 99%
“…9b and c. Recent visible near-field studies of quasi-periodic structures have revealed focus spots at a significant distance away from the surface (5 µm) with widths less than half the optical wavelength [132]. Fractal aperture patterns in metal films have been investigated for their ability to show resonances over a broader wavelength range due to their self-similar structure [133].…”
Section: Lattice Effectsmentioning
confidence: 99%